Penerapan model pembelajaran kooperatif tipe aktif, kolaborasi, dan induktif dalam meningkatkan kemampuan generalisasi matematis siswa SMP - Nirfayanti, Nirfayanti; Syamsuriyawati, Syamsuriyawati; Aisyah, Nur (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2024)
The mathematical generalization ability of students at one junior high school, especially in Makassar, is relatively low. One alternative to improve students' mathematical generalization abilities is to apply active, collaborative and inductive cooperative learning models. This research aims to determine the difference in the average score of mathematical generalization abilities of students taught through active, collaborative and inductive cooperative learning models, and students taught through cooperative learning models on flat-sided geometric material. This research used a quasi-experimental design with a pretest-posttest control group design in class VIII at a junior high school in Makassar, Indonesia. The sample in this study was 35 students in the control group and 31 students in the experimental group. The instrument used is a mathematical generalization ability test. Data were analyzed using the n gain test. Based on the analysis, the average n-gain score for students' mathematical generalization abilities in flat-sided geometric material after being taught by applying active, collaborative and inductive cooperative learning models was 0,51 or experienced a moderate increase and the percentage of learning completeness was 93,55%. Therefore, it can be concluded that junior high school students' mathematical generalization abilities increased after being taught using active, collaborative and inductive cooperative learning models.